ANALISIS STRATEGI PENGEMBANGAN DESTINASI WISATA PANTAI ROR BUKIT TINGGI DI KABUPATEN MINAHASA UTARA - Tedy Valens Silape; Chabelita B. E. Panigoro (Jurnal Ilmu Pariwisata, 2024)
The purpose of this study is to develop and analyze the development strategy of ROR Bukit Tinggi Beach tourist destinations in North Minahasa Regency. The analysis method used in this study is a qualitative descriptive method that aims to explore and understand complex phenomena. The data collection technique uses observation methods, conducting interviews and making important documentation. The results of this study found that the SWOT Analysis Matrix clarifies all factors of strengths, weaknesses, opportunities, and threats that can be identified in an effort to provide a clear picture of the development of ROR beach tourist attractions.